2017
DOI: 10.1016/j.saa.2016.04.025
|View full text |Cite
|
Sign up to set email alerts
|

Ageing studies of TPB in noble gas detectors for dark matter and neutrinoless ββ decay searches

Abstract: Noble gases (Xe, Ar, Kr) are very attractive as detector media in Dark Matter search and neutrinoless double-beta decay experiments. However, the detection of their scintillation light (in the VUV spectral region) requires shifting the VUV light to visible light, where standard photosensors are more efficient. Tetraphenyl butadiene (TPB) is widely used as wavelength shifter, absorbing the VUV light and re-emitting in the blue region (~430 nm). TPB is an organic molecule that may degrade due to exposure to envi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 9 publications
(14 reference statements)
2
2
0
Order By: Relevance
“…Yahlali et al [98] demonstrated, however, that the conversion efficiency loss after exposure to VUV light comparable with that integrated over a ∼5 year lifetime of a typical experiment does not exceed 15%, which is consistent with the results of, e.g., GERDA, DEAP-1, DEAP-3600 or DarkSide-50. Furthermore, a thick TPB coating (1.6 µm) had stronger resistance to VUV radiation damage than a thin coating (130 nm).…”
Section: Tpbsupporting
confidence: 72%
“…Yahlali et al [98] demonstrated, however, that the conversion efficiency loss after exposure to VUV light comparable with that integrated over a ∼5 year lifetime of a typical experiment does not exceed 15%, which is consistent with the results of, e.g., GERDA, DEAP-1, DEAP-3600 or DarkSide-50. Furthermore, a thick TPB coating (1.6 µm) had stronger resistance to VUV radiation damage than a thin coating (130 nm).…”
Section: Tpbsupporting
confidence: 72%
“…Yahlali et al [96] demonstrated, however, that the conversion efficiency loss after exposure to VUV light comparable with that integrated over a ∼5 year lifetime of a typical experiment does not to exceed 15%, which is consistent with the results of e.g. GERDA, DEAP-1, DEAP-3600 or DarkSide-50.…”
Section: Tpbsupporting
confidence: 72%
“…The conversion efficiency of vacuum-evaporated TPB-coatings as a function of thickness and their ageing effects when exposed to VUV light at the xenon scintillation wavelength is reported in ref. [7]. The tracking plane of NEW is instrumented with about 1800 SiPMs SensL MicroFC-10035-SMT-GP, arranged in 28 Kapton boards (KB) as shown in figure 2-right, temperature sensors (NTC) and one LED for calibration.…”
Section: The Sipm Readout Technique In Nextmentioning
confidence: 99%